2021
DOI: 10.1042/bst20210325
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the multifunctionality of SR proteins

Abstract: Members of the arginine–serine-rich protein family (SR proteins) are multifunctional RNA-binding proteins that have emerged as key determinants for mRNP formation, identity and fate. They bind to pre-mRNAs early during transcription in the nucleus and accompany bound transcripts until they are translated or degraded in the cytoplasm. SR proteins are mostly known for their essential roles in constitutive splicing and as regulators of alternative splicing. However, many additional activities of individual SR pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 101 publications
0
22
0
Order By: Relevance
“…A number of proteins can be classified as SR-related proteins even though they lack RNA binding activity and do not seem to be involved (at least directly) in RNA splicing (Long and Caceres 2009). Previous studies have suggested that SR/SR-related proteins can also be involved in a variety of peripheral functions unrelated to RNA splicing, including nucleocytoplasmic shuttling, translation, chromatin organization, cell cycle regulation, and metabolism (Shepard and Hertel 2009;Giannakouros et al 2011;Long and Caceres 2009;Wagner and Frye 2021;Zhong et al 2009;Slišković, et al 2022). Given the overwhelming abundance of RNA splicing proteins among SR/SR-related proteins and the diversity of nonsplicing functions among SR/SR-related proteins, these peripheral functions would likely not be enriched enough to reach statistical significance in GO term analyses, but may nevertheless suggest subclasses of SR-related proteins associated with specific processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of proteins can be classified as SR-related proteins even though they lack RNA binding activity and do not seem to be involved (at least directly) in RNA splicing (Long and Caceres 2009). Previous studies have suggested that SR/SR-related proteins can also be involved in a variety of peripheral functions unrelated to RNA splicing, including nucleocytoplasmic shuttling, translation, chromatin organization, cell cycle regulation, and metabolism (Shepard and Hertel 2009;Giannakouros et al 2011;Long and Caceres 2009;Wagner and Frye 2021;Zhong et al 2009;Slišković, et al 2022). Given the overwhelming abundance of RNA splicing proteins among SR/SR-related proteins and the diversity of nonsplicing functions among SR/SR-related proteins, these peripheral functions would likely not be enriched enough to reach statistical significance in GO term analyses, but may nevertheless suggest subclasses of SR-related proteins associated with specific processes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent mechanistic model of splicing proposed that these activities enable a complex splicing logic at the nuclear speckle interface, suggesting that the biophysical properties and behavior of RS domains are important features influencing splicing activity (Liao and Regev 2021). Additionally, although SR proteins are typically associated with splicingrelated functions, these proteins participate in a wide variety of cellular processes, including nucleocytoplasmic shuttling, translation, chromatin organization, cell cycle regulation, and metabolism (Giannakouros et al 2011;Mueller and Hertel 2012;Shepard and Hertel 2009;Long and Caceres 2009;Wagner and Frye 2021;Zhong et al 2009;Slišković, et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, overexpression of SRSF1 alters the splicing pattern of HIV-1 mRNA (increases the Vpr mRNA and decreases Env mRNA), inhibits Gag and Env protein synthesis, and consequently, virion production [15]. The sequences and structural similarities between SRSF1 and SRSF9 are high according to the phylogenetic tree of the SR protein family aligned by mafft, v7, L-INS-I method [33]. This, SRSF9 could also regulate alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, overexpression of SRSF1 disrupt the balance of alternative splicing of viral mRNA, inhibits Gag and Env protein synthesis, and consequently, virion production ( 15 ). The sequences and structural similarities between SRSF1 and SRSF9 are high according to the phylogenetic tree of the SR protein family aligned by mafft, v7, L-INS-I method ( 33 ). This, SRSF9 could also regulate alternative splicing.…”
Section: Discussionmentioning
confidence: 99%